2001
DOI: 10.1038/88889
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated expression of c-Myc depletes epidermal stem cells

Abstract: The beta-catenin/TCF signaling pathway is essential for the maintenance of epithelial stem cells in the small intestine. c-Myc a downstream target of beta-catenin/TCF (ref. 2), can induce differentiation of epidermal stem cells in vitro. To determine the role of c-Myc in epidermal stem cells in vivo, we have targeted expression of human MYC2 to the hair follicles and the basal layer of mouse epidermis using a keratin 14 vector (K14.MYC2). Adult K14.MYC2 mice gradually lose their hair and develop spontaneous ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
297
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(333 citation statements)
references
References 23 publications
35
297
0
1
Order By: Relevance
“…M2SMO samples did not contain detectable levels of Shh mRNA, arguing that the appearance of sebocytes in transgenic skin was not the result of up-regulated Shh expression. In light of recent studies documenting enhanced sebocyte development in mice expressing MYC in skin, 36,37 it is noteworthy that c-Myc expression appeared to be up-regulated in volar skin of M2SMO mice, compared to controls.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…M2SMO samples did not contain detectable levels of Shh mRNA, arguing that the appearance of sebocytes in transgenic skin was not the result of up-regulated Shh expression. In light of recent studies documenting enhanced sebocyte development in mice expressing MYC in skin, 36,37 it is noteworthy that c-Myc expression appeared to be up-regulated in volar skin of M2SMO mice, compared to controls.…”
Section: Resultsmentioning
confidence: 90%
“…The potential influence of cross-talk involving Hedgehog and Wnt 49 or BMP 50 pathways will also need to be examined. In addition, it will be important to explore the relationship between the Hedgehog pathway and other molecules implicated in sebocyte development, including c-Myc, 36,37 PPAR␥, 51,52 and COX-2. 53 Hair follicles and sebaceous glands both undergo cyclic changes after birth, 54 and Shh plays a major role in regulating proliferation of follicle epithelium during times of active growth.…”
Section: Discussionmentioning
confidence: 99%
“…31 Interestingly, ectopic expression of MYC in the basal layer of the murine epidermis causes depletion of stem cells and increased differentiation. 39,40 Furthermore, this exit from the stem cell compartment has been linked to repression of adhesion genes and the disruption of critical interactions between stem cells and their specified microenvironment or "niche." 41,42 Most notably, repression of these genes has already been shown to depend on association with MIZ1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have underlined the important role of MYC in the differentiation of skin epithelium (Pelengaris et al, 2002;Alonso and Fuchs, 2003). Through the depletion of integrin b (Waikel et al, 2001), MYC was found to act selectively on epidermal stem cells (Gandarillas and Watt, 1997), driving them into the transit amplification compartment and stimulating differentiation into interfollicular epidermis and sebocytes (Frye et al, 2003). In an experimental model, MYC activation was sufficient to induce a neoplastic phenotype in the skin (Pelengaris et al, 1999).…”
Section: Discussionmentioning
confidence: 99%